An Educational Intervention to Mothers Improved the Nutritional Status of Mexican Children Younger Than 5 Years Old With Mild to Moderate Malnutrition - Sonia Sánchez-Encalada MSc; Myrna Mar Talavera-Torres MD; Rosa Maria Wong-Chew MD, DSc (SAGE Publishing, 2019)
Malnutrition in children younger than 5 years old has persisted in time (13.5% in 1988 to 12.3% in 2012) in Mexico City. A quasi-experimental study was performed. An educational intervention was given twice a month for 6 months to mothers of mild to moderate malnourished children 1 to 5 years old. Weight, height, and body mass index of the children were obtained at the beginning and 3 and 6 months after the intervention. Thirteen mothers and 15 children were included. The baseline mean weight/age in Z score was −1.49 ± 0.65, which improved to −1.19 ± 0.60 ( P = 0.001; per protocol analysis). Linear regression analysis showed a P of 0.006 of the mothers' adherence to improve children's weight. The educational intervention decreased the weight deficit after 6 months with the same economic resources of the family; hence, the adherence of the mothers to the educational intervention is relevant to improve the nutritional status of their children.